Răspuns:
Explicație pas cu pas:
[tex]\large \bf a)~~ [(-3)^{7}]^{2}:(-3)^{11}+(-2)^{4} =[/tex]
[tex]\large \bf (-3)^{7\cdot 2}:(-3)^{11}+2^{4} =[/tex]
[tex]\large \bf (-3)^{14}:(-3)^{11}+2^{4} =[/tex]
[tex]\large \bf (-3)^{14-11}+2^{4} =[/tex]
[tex]\large \bf (-3)^{3}+2^{4} =[/tex]
[tex]\large \bf -27+16 =[/tex]
[tex]\color{red}\Large \boxed{\bf -11}[/tex]
[tex]\large \bf b)~~ 100:(-10):(-5)+4\cdot(-4)+(-5)^{2} =[/tex]
[tex]\large \bf -10:(-5)-16+5^{2} =[/tex]
[tex]\large \bf 2-16+5^{2} =[/tex]
[tex]\large \bf 2-16+25 =[/tex]
[tex]\color{blue}\Large\boxed{ \bf 11}[/tex]
#copaceibrainly